AKTA KELAHIRAN ANAK LUAR KAWIN SEBAGAI HAK PERDATA ANAK - Maria Rosalina (Fakultas Hukum universitas Islam Sumatera Utara, 2020)
Abstract Marriage is a physical and mental bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family or household based on the One Godhead. One of the goals of marriage is to have offspring, namely children, who are the successors of the family. Article 2 Paragraph (2) Law No. 1 Year 1974 states